-m-2=-6m-62

Simple and best practice solution for -m-2=-6m-62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m-2=-6m-62 equation:


m in (-oo:+oo)

-m-2 = -6*m-62 // + -6*m-62

62-m-(-6*m)-2 = 0

6*m-m-2+62 = 0

5*m+60 = 0 // - 60

5*m = -60 // : 5

m = -60/5

m = -12

m = -12

See similar equations:

| -10-3w=w-58 | | t+8=-40-7t | | 5b-1=2b-28 | | 3n+2=-7n+122 | | 4d+2=2d+2 | | 7b+10=2b+55 | | 6w+5=-5w+71 | | 2d+2=-2d+10 | | 3n-1=-2n+34 | | 7w+9=w+81 | | -3-4m=3m-17 | | 3a-6=6a-21 | | 8-4a=5a-1 | | 8+6t=2t-12 | | 5n+6=-22+n | | 3-2t=4t-15 | | 7b+2=b+8 | | 7w-7=-2w-88 | | -7t-5=-16-6t | | -7+d=7d+41 | | -7n+9=-n+9 | | -5d+7=2d+63 | | 5-2k=5k+89 | | 9-3b=b+53 | | 7m-2=26+3m | | 3t+2=6+5t | | 7n+8=20+4n | | -6n-6=-21-n | | -7x-9=3x-119 | | 3t+4=58-3t | | 7k+7=-3k-23 | | 10+2t=5t-5 |

Equations solver categories